2022
DOI: 10.1126/scitranslmed.abp9675
|View full text |Cite
|
Sign up to set email alerts
|

Human β-defensin 2 ameliorates acute GVHD by limiting ileal neutrophil infiltration and restraining T cell receptor signaling

Abstract: Acute graft-versus-host disease (aGVHD), which is driven by allogeneic T cells, has a high mortality rate and limited treatment options. Human β-defensin 2 (hBD-2) is an endogenous epithelial cell–derived host-defense peptide. In addition to its antimicrobial effects, hBD-2 has immunomodulatory functions thought to be mediated by CCR2 and CCR6 in myeloid cells. In this study, we analyzed the effect of recombinant hBD-2 on aGVHD development. We found that intestinal β-defensin expression was inadequately induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Therefore, it does not rule out the potential role of altered ileal microbiota composition in the mechanism of barrier dysfunction in irradiated mice. A recent study showed that another antimicrobial peptide, human β-defensin-2, modulated intestinal microbiota composition and attenuated neutrophil infiltration in a graft-versus-host disease model, suggesting a potential direct effect of this peptide on the intestinal mucosa ( 75 ). The antibacterial effect of HD5 is attributed to the creation of pores on the bacterial plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it does not rule out the potential role of altered ileal microbiota composition in the mechanism of barrier dysfunction in irradiated mice. A recent study showed that another antimicrobial peptide, human β-defensin-2, modulated intestinal microbiota composition and attenuated neutrophil infiltration in a graft-versus-host disease model, suggesting a potential direct effect of this peptide on the intestinal mucosa ( 75 ). The antibacterial effect of HD5 is attributed to the creation of pores on the bacterial plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, hBD-2 has been found to reduce proinflammatory cytokines, such as interleukin 1-β (IL1-β) and TNF-α (TNF) in LPS-treated human peripheral blood mononuclear cells (PBMCs) [ 38 ]. Furthermore, oral administration of hBD-2 reduced both alcohol-induced liver injury and graft-versus-host disease, in numerous mouse strains, by improving barrier function and thereby modulating host–microbe interactions and immunoreactivity [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“… 262 In addition, a recent study reported that hBD2 ameliorates acute graft–versus–host disease (aGvHD) through regulating the gut microbiome to limit ileal neutrophil infiltration and restrain T-cell receptor signaling. 263 Tamima and colleagues found that induction of hBD2 is impaired in cases of aGVHD in both humans and mice. However, when hBD2 was administered, the severity and mortality of aGVHD were reduced.…”
Section: The Biological Functions Of Defensinsmentioning
confidence: 99%